Study of effects of sleeve grouting defects on the seismic performance of precast concrete shear walls. (1st June 2021) - Xiao, Shun; Wang, Zhuolin; Li, Xiangmin; Harries, Kent A.; Xu, Qingfeng; Gao, Rundong
Highlights: Defect-free grouted sleeve wall panels were equivalent to monolithic-cast walls having continuous bars. Grout sleeve defects adversely affect wall behavior – primarily when the spliced bar is in tension. The degree of the defect impacts the force the bar can develop. Panels that achieved at least 92% of their capacity were indistinguishable from defect-free panels. Noticeable loss of performance was evident at wall panel capacities of 85% and lower. Abstract: Precast concrete wall systems are effective means of resisting seismic forces in many structures. However, their performance is affected by the ability to properly connect elements – usually with grout sleeves. Grout sleeve connections are known to be susceptible to backflow during grouting resulting in partially grouted or occasionally entirely ungrouted sleeves. In this study an investigation of the impact of sleeve grouting defects on the seismic performance of precast concrete shear walls is presented. Grouting defects of different sizes and at different positions in the walls were intentionally introduced. Reversed cyclic loading tests of precast concrete shear wall specimens and a comparable monolithically cast-in-place concrete shear wall specimen were performed. The defect-free grouted sleeve panels were shown to be equivalent to monolithic cast walls having continuous bars in terms of capacity although, due to the short sleeve embedment, the precast walls are less stiff and therefore demonstrate reduced ductility. Energy dissipation, however is similar and both monolithically cast and precast walls meet the requirements for use as seismic resistant systems. The study showed that grout sleeve defects adversely affect wall behavior – primarily when the spliced bar is in tension. The impact of defects can be assessed through standard design equations by assuming that the degree of the defect impacts the force the bar can develop. As demonstrated in this study, wall performance becomes an issue of quantifying and predicting defects and their effect, not on the individual bars, but on the wall panel assembly. The panels in this study were dominated by flexural behavior; thus the reduction in panel moment capacity provides a means of differentiating behavior. Panels that maintained at least 92% of their theoretical flexure capacity were mostly indistinguishable from defect-free panels. Noticeable loss of performance was evident at panel capacities of 85% and lower.